2017
DOI: 10.1007/s10654-017-0269-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare and disease burden among refugees in long-stay refugee camps at Lesbos, Greece

Abstract: This study can help policy makers and Non-Governmental Organizations decide which health care is needed most in the current European refugee crisis. There is an urgent need for mental and dental healthcare. Furthermore, it is crucial that vaccination programs are initiated and "hotspot" camps should transform in camps designed for long-stay situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 5 publications
0
78
1
6
Order By: Relevance
“…Health screening in refugees arriving at the Greek border with Turkey showed that respiratory tract infections were the most common medical problem, diagnosed with a prevalence of 23% in 6899 migrants [35,36]. Another study detected respiratory tract infections in 41% of 33,331 patients who accessed care points of entry into Greece and Serbia [16,17,36,37].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
See 4 more Smart Citations
“…Health screening in refugees arriving at the Greek border with Turkey showed that respiratory tract infections were the most common medical problem, diagnosed with a prevalence of 23% in 6899 migrants [35,36]. Another study detected respiratory tract infections in 41% of 33,331 patients who accessed care points of entry into Greece and Serbia [16,17,36,37].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
“…Outbreaks are generally more severe in refugee camps [48]. Sharing dormitories, a lack of accessible toilet facilities, poor hygiene conditions, undernourishment, and limited access to medical care were reported as factors contributing to the increased susceptibility to disease [35,49]. Children and the elderly are undoubtedly particularly vulnerable [50,51,52].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
See 3 more Smart Citations